1986
DOI: 10.1128/mcb.6.5.1796
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate regulation of myelomonocytic phenotype by v-myb and v-myc.

Abstract: Both avian myeloblastosis virus (by the action of v-myb) and avian myelocytomatosis virus MC29 (by the action of v-myc) transform cells of the myelomonocytic lineage. Whereas avian myeloblastosis virus elicits a relatively immature phenotype, cells transformed by MC29 resemble mature macrophages. When cells previously transformed by v-myb were superinfected with MC29, their phenotype was rapidly altered to that of a more mature cell. These superinfected cells expressed both v-myb (at a level similar to that fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
(57 reference statements)
0
9
0
Order By: Relevance
“…To identify target genes for v-Myc in myelomonocytic cells, we searched for genes differentially expressed between the avian myeloblastosis virus-transformed chicken myeloblast cell line BM2 (26) and subclones of this line infected with the chicken retrovirus MC29 (27). To our surprise, by simply comparing the expression of known genes in these cells, we identified several genes whose expression was down-regulated by v-Myc.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify target genes for v-Myc in myelomonocytic cells, we searched for genes differentially expressed between the avian myeloblastosis virus-transformed chicken myeloblast cell line BM2 (26) and subclones of this line infected with the chicken retrovirus MC29 (27). To our surprise, by simply comparing the expression of known genes in these cells, we identified several genes whose expression was down-regulated by v-Myc.…”
Section: Resultsmentioning
confidence: 99%
“…BM2 is a line of avian myeloblastosis virustransformed chicken myeloblasts (26). Infection of BM2 cells with MC29 virus has been described (27) (30) and encodes the MC29-specific Gag-Myc fusion protein. pMC29(Q10-4)Notfs is a derivative of pMC29(Q10-4) carrying a frameshift at a unique NotI restriction site in the v-myc-coding region.…”
Section: Methodsmentioning
confidence: 99%
“…One of the hallmarks of v-Myc and c-Myc is the ability to interfere with differentiation processes, particularly of cells, such as myelomonocytic cells or adipocytes, whose differentiation is dependent on C/EBP factors (Symonds et al, 1986;Hoffman-Liebermann and Liebermann, 1991;Freytag and Geddes, 1992;Heath et al, 2000). Earlier, we have shown that v-Myc inhibits the transactivation potential of several C/EBP family members (Mink et al, 1996), suggesting that C/EBPs are crucial targets for Myc in C/EBPdependent differentiation processes.…”
Section: Introductionmentioning
confidence: 99%
“…We were therefore interested to see whether an e ect of v-Myc on ATF2 could also be observed under more physiological conditions. To address this question we analysed the amount and phosphorylation state of (Symonds et al, 1986) and have been used before to demonstrate the inhibitory e ect of Myc on the expression of C/EBP regulated genes (Mink et al, 1996). As shown by Western blotting, both the amount of total ATF2 as well as of phosphorylated ATF2 was increased in the BM2(MC29)cl.4 cells compared to the original BM2 line.…”
Section: Myc Induces the Phosphorylation Of Gal4/atf2mentioning
confidence: 99%
“…BM2 is a line of avian myeloblastosis virus transformed chicken myeloblasts (Moscovici et al, 1982). BM2(MC29)cl.4 is a derivative of the BM2 line obtained by infecting BM2 cells MC29 virus (Symonds et al, 1986). BM2 and BM2(MC29) cells were grown in RPMI 1640 medium supplemented with 10% (vol/vol) tryptose phosphate broth, 5% (vol/vol) fetal calf serum and 5% (vol/vol) chicken serum.…”
Section: Cell Linesmentioning
confidence: 99%